2009
DOI: 10.1073/pnas.0808529106
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast ribonucleoprotein CP31A is required for editing and stability of specific chloroplast mRNAs

Abstract: Chloroplast ribonucleoproteins (cpRNPs) are nuclear-encoded, highly abundant, and light-regulated RNA binding proteins. They have been shown to be involved in chloroplast RNA processing and stabilization in vitro and are phylogenetically related to the well-described heterogeneous nuclear ribonucleoproteins (hnRNPs). cpRNPs have been found associated with mRNAs present in chloroplasts and have been regarded as nonspecific stabilizers of chloroplast transcripts. Here, we demonstrate that null mutants of the cpR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 40 publications
1
100
0
1
Order By: Relevance
“…Immunodepletion of CP31 from the editing extract resulted in the inhibition of editing of psbL and ndhB mRNAs. More recently, a null mutant of CP31A, one of the two paralogues found in Arabidopsis, was shown to exhibit multiple specific editing defects in chloroplast transcripts (43). However, Tillich et al (43) also observed that CP31 was responsible for the stability of specific chloroplast mRNAs, because almost no ndhF mRNA could be detected, and other chloroplast mRNAs were also depleted in cp31a mutants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Immunodepletion of CP31 from the editing extract resulted in the inhibition of editing of psbL and ndhB mRNAs. More recently, a null mutant of CP31A, one of the two paralogues found in Arabidopsis, was shown to exhibit multiple specific editing defects in chloroplast transcripts (43). However, Tillich et al (43) also observed that CP31 was responsible for the stability of specific chloroplast mRNAs, because almost no ndhF mRNA could be detected, and other chloroplast mRNAs were also depleted in cp31a mutants.…”
Section: Discussionmentioning
confidence: 97%
“…The editing defect in cp31a mutant and the cp31a/ cp31b double mutant is much less severe than ones that we observed in the orrm1 mutant; an edited peak was detectable in the electrophoretograms of RT-PCR bulk sequences surrounding the editing sites most affected in cp31a/cp31b mutant (figure S2 in ref. 43). Bulk sequencing is a much less sensitive editing assay than either RNA-seq or PPE.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ORRM1, another RRM protein, CP31, was suggested to be involved in RNA editing in plastids. 46,74 The editing machinery in plastids may be more complicated than we previously estimated in the two-component model. 34 In addition to a transfactor, the MORF2/MORF9 heterodimer is also necessary for almost all editing sites in plastids.…”
Section: Function Of Ppr Proteins In Plastid Gene Expressionmentioning
confidence: 85%
“…Then, pulses (0.8 s) of white light (5000 mmol photons m 22 s 21 ) were used to determine the maximum fluorescence (Fm). The transient increase in fluorescence was recorded after a 5-min exposure to actinic light (80 mmol photons m 22 s 21 ; as previously described in Tillich et al, 2009). ETR and NPQ of Arabidopsis leaves and in vivo chlorophyll a fluorescence of whole P. patens plants were recorded using the Imaging PAM (Walz).…”
Section: Chlorophyll Fluorescence Analysismentioning
confidence: 99%
“…In vivo chlorophyll a fluorescence of Arabidopsis leaves was measured using the pulse amplitude modulation 101/103 instrument (PAM 101/103; Walz) as described (Varotto et al, 2000;Tillich et al, 2009). Plants were dark-adapted for 30 min, and minimal fluorescence (Fo) was measured.…”
Section: Chlorophyll Fluorescence Analysismentioning
confidence: 99%